2016
DOI: 10.4103/2211-4122.192175
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic challenge of dipyridamole-atropine stress echocardiography in a patient with myocardial bridge

Abstract: A 60-year-old male patient was submitted to dipyridamole-atropine stress echocardiography (DSE) for chest pain during exertion. At rest, no electrocardiographic (ECG) and transthoracic echocardiographic (TTE) abnormalities were observed. After dipyridamole infusion, the patient complained a mild chest discomfort, without ECG changes and TTE wall-motion abnormalities. Subsequently, worsening of the anginal symptoms combined with descending ST-depression and T-negative waves occurred after atropine and unexpecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 7 publications
0
3
0
Order By: Relevance
“…Coronary angiography was performed showing a MB of the left anterior descending artery. 14 The MB prevalence during coronary angiography varies, ranging from 0.5 to 16%. 15 Matta et al, in a study of 35,000 patients referred for coronary angiography between June 2012 and June 2020, reported that MB of the LAD occurred in 1.42% of the study population.…”
Section: Discussionmentioning
confidence: 99%
“…Coronary angiography was performed showing a MB of the left anterior descending artery. 14 The MB prevalence during coronary angiography varies, ranging from 0.5 to 16%. 15 Matta et al, in a study of 35,000 patients referred for coronary angiography between June 2012 and June 2020, reported that MB of the LAD occurred in 1.42% of the study population.…”
Section: Discussionmentioning
confidence: 99%
“…A case of myocardial bridge (MB) was reported in a previous issue of the Journal of Cardiovascular Echography. [ 1 ]…”
mentioning
confidence: 99%
“…described a case of MB with positive dipyridamole stress test and mechanical cardiac alteration highlighted by speckle tracking echocardiography (STE). [ 1 ] Even if patient complained of mild chest discomfort at the end of dipyridamole infusion, neither electrocardiographic (ECG) changes nor wall motion abnormalities occurred. Subsequently, to the administration of atropine, it was possible to observe mild ECG changes and lower longitudinal strain of the anterior interventricular septum, with a more pronounced ST depression and T-wave inversion in V2–V4 only after aminophylline was administered.…”
mentioning
confidence: 99%